INFLUENCE OF TIERED LESSON AND GROUP PERSONALIZATION INSTRUCTIONAL STRATEGIES ON SENIOR SECONDARY SCHOOL STUDENTS’ ACHIEVEMENT IN MATHEMATICS - Fisayo Areelu; Mojeed Kolawole Akinsola (European Scientific Journal, ESJ, 2014)
This study examined the Effects of Tiered Lesson Instructional Strategy (TLIS) and Group Personalization Instructional Strategies (GPIS) on Senior Secondary School Students Achievement in Mathematics. The moderating effects of mathematics anxiety and gender were also investigated. The study adopted the pretest-posttest, control group, quasi experimental design with a 3x3x2 factorial matrix. Three hundred and thirtyseven senior secondary two students from six public schools purposively selected participated in the study. Four null hypotheses were tested at 0.05 significance level. Four instruments were developed, validated and used for data collection. Data were analysed using Analysis of Covariance and Scheffe Post hoc test. The findings showed that treatment had significant effect on students’ achievement in Mathematics (F (2,318) =324.73, p<.05). Students exposed to TLIS had the highest post achievement score. The study also revealed that Mathematics Anxiety (MA) had significant effect on Students’ achievement in Mathematics (F (3,333)=122.54,p<.05). Students with low MA had the highest post achievement score. It also showed that gender had no significant effect on students’ achievement in Mathematics. Furthermore, the result of the 3-way interactions showed a significant interaction effects of treatment, mathematics anxiety and gender on students’ achievement in Mathematics (F(18,318) = 2.063, p < 0.05). Among the students in the TLIS group, those with low MA had highest post achievement scores. It was concluded that Mathematics teachers should be trained to use tiered lesson and group personalization learning packages in the classroom, since the strategies are effective in enhancing students’ achievement in Mathematics than the conventional method.